Comparative Analysis of Transaction Costs and Borrowers Perceptions of Credit Loan Procedures at Financial Institutions - Suryadi, Sasri; Rifai, Ahmad; Muwardi, Didi (Politeknik Pertanian Negeri Payakumbuh, 2022)
Financial institutions have different goals and motivations; as such Cooperatives and Village-Owned Enterprises, resulting in differences in determining loan procedures, loan terms, transaction cost components, transaction costs. This condition inevitably influences customer perceptions of credit loans. This research was conducted in Sei Lambu Makmur Village, Tapung District, Kampar Regency. Borrower's perceptions analysis is measured using an ordinal scale, which is guided by the Likert's Summated Rating Scale (LSRS). The results of the study explained that there were differences in the transaction cost components of financial institutions in Desa Sei Lambu Makmur, the BUMDes Makmur Bersama Savings and Loans business unit was more efficient in determining loan transaction costs, perceptions of borrowers in the BUMDes Makmur Bersama Savings and Loans business unit and the borrowers of Mekar Jaya Palm Oil Cooperatives including into the good category.